Pola Komunikasi Organisasi Pimpinan dan Karyawan dalam Meningkatkan Kinerja : (Studi Kasus di Yayasan Rahmatan Lil-Alamin Jakarta Timur) - Dadan Ramdani; Ade Fadli Fachrul (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2025)
The purpose of this study is to determine the organizational communication pattern of leaders and employees at Yayasan Rahmatan Lil-Alamin Jakarta Timur and their relationship in improving their performance at work. The research method used in this study is a qualitative research method. The research location is at the Central Secretariat Office of Yayasan Rahmatan Lil-Alamin Jakarta Timur, and at Kantor Layanan Donasi Yayasan Rahmatan Lil-Alamin Jakarta Timur. The time of the research was carried out on August 25 - September 31, 2021. The informants in this study were the General Chairperson, the HR/HRD Division, and three employees at Yayasan Rahmatan Lil-Alamin Jakarta Timur. Data collection techniques consist of observation, interviews, and documentation. Methods of data analysis using descriptive qualitative method. The results of the study conclude that the communication that occurs at Yayasan Rahmatan Lil-Alamin Jakarta Timur is a chain communication pattern that is carried out formally from top to bottom and bottom to top. In improving the performance of its employees, the committee of the foundation conducts evaluations, briefings, and motivations for employees as well as holding non-formal agendas such as family gatherings, camping, or joint sports. The obstacles that occur consist of miscommunication, namely errors in understanding the messages conveyed based on different mindsets, physical barriers such as network and communication disturbances, as well as structural and procedural barriers that require employees to submit inputs or complaints to third parties.